Potential Comparative Advantages of Manufactured Products Sudan vis-à-vis Egypt - منوفلي، عباس حسن (جامعة كسلا, 2017)
تهدف هذه الدراسة إلى بحث إمكانية تحقيق ميزات نسبية للمنتجات المصنعة محليا في جمهورية السودان في نطاق التجارة مع مصر. الدراسة مبنية على الأسعار النسبية كمؤشرات للميزات النسبية المحتملة. تم احتساب الأسعار النسبية لعدد 29 سلعة من المنتجات المصنعة محليا في فبراير 2016 م وهي من السلع الاستهلاكية المشمولة في سلة حساب مؤشر أسعار المستهلكين في السودان. وتم أيضا احتساب الأسعار النسبية لاثنتين من السلع الاستهلاكية/ الإنتاجية (وهي حديد التسليح والإسمنت). تشير النتائج إلى أن السودان قد تكون له ميزات نسبية في 7 من السلع الاستهلاكية المصنعة التي شملتها الدراسة. كما تشير النتائج إلى أن السودان قد تكون له ميزة نسبية في إنتاج حديد التسليح، في حين أن مصر لديها ميزة نسبية في الإسمنت. من أهم توصيات الدراسة ضرورة تعزيز الميزات النسبية للمنتجات المصنعة في السودان من خلال اتخاذ السياسات اللازمة لحل المشكلات الرئيسة التي تواجه قطاع الصناعات التحويلية، خاصة ارتفاع تكاليف الإنتاج والضرائب والرسوم وعدم انتظام إمداد الطاقة الكهربائية، وذلك بالإضافة إلى تعزيز تسويق المنتجات التي قد يكون للسودان ميزات نسبية في إنتاجها. This study is an endeavor to investigate the potentiality of having comparative advantages of locally manufactured products in the Republic of Sudan vis-à-vis Egypt. It is based on relative prices as signals for potential comparative advantages. Relative prices are calculated for 29 locally produced manufactured products in February 2016. Such products are mainly consumer goods included in the basket for calculating CPI in Sudan. Also relative prices of two consumer/producer goods (namely structural steel and cement) are calculated. The results indicate that Sudan may have comparative advantages in 7 of the 29 consumer manufactured goods included in the study. The results on steel and cement indicate that Sudan may have comparative advantage in the production of structural steel, while Egypt has comparative advantage in cement. One of the recommendations on the basis of the results is to strengthen comparative advantages in Sudan by undertaking necessary policies for solving the major problems facing the manufacturing sector, mainly high costs of production, taxes and fees, and interrupted electric power supply, beside strengthening the marketability of the products in which Sudan may have comparative advantages.
Keywords: التجارة الدولية -- السلع الاستهلاكية -- الصناعات التحويلية -- مصر